Wheat middlings in high concentrate finishing rations: cattle performance - Dalke, B.S.; Sonon, R.N. Jr.; Holthaus, D.L.; Bolsen, K.K.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred twenty medium-framed steers were fed one of six high (90%) concentrate rations: control (0), 5, 10, or 15% pelleted wheat middlings (WM) replacing the concentrate (dry rolled corn) and 5 or 10% pelleted WM replacing the roughage (chopped alfalfa hay). Increasing WM replacement of the concentrate increased both dry matter (DM) intake and feed/gain ratio linearly, without influencing daily gain or final weight. WM replacement of the roughage decreased DM intake linearly, but it ha d no effect on daily gain, final weight, or feed efficiency . The data indicate that WM could replace only 5% of the concentrate without reducing cattle performance, but complete (100%) or partial (50%) replacement of the roughage with WM had no adverse effect on cattle performance.
Keywords: Beef; Wheat middlings; Beef cattle; Performance; Feedlot